1. ## testing

$g(x) = \left\{
\begin{array}{c l}
x^2 + x + 1 & x \in (-1,0]\\
x^2 + x & x \in (0,1)\\
x^2 & x \not\in (-1,1)
\end{array}
\right.
$

$g(x) = \left\{
\begin{array}{c l}
0 & x \in (-1,0]\\
x^2 + x & x \in (0,1)\\
x^2 & x \not\in (-1,1)
\end{array}
\right.
$

2. ## Re: testing

Originally Posted by hmmmm
$g(x) = \left\{
\begin{array}{c l}
x^2 + x + 1 & x \in (-1,0]\\
x^2 + x & x \in (0,1)\\
x^2 & x \not\in (-1,1)
\end{array}
\right.
$

$g(x) = \left\{
\begin{array}{c l}
0 & x \in (-1,0]\\
x^2 + x & x \in (0,1)\\
x^2 & x \not\in (-1,1)
\end{array}
\right.
$
Remove all line-feeds.
[TEX]g(x) = \left\{\begin{array}{c l} x^2 + x + 1 & x \in (-1,0]\\ x^2 + x & x \in (0,1)\\ x^2 & x \not\in (-1,1)\end{array}\right.[/TEX]
gives
$g(x) = \left\{\begin{array}{c l} x^2 + x + 1 & x \in (-1,0]\\ x^2 + x & x \in (0,1)\\ x^2 & x \not\in (-1,1)\end{array}\right.$

3. ## Re: testing

Hello, all!

By accident I found a way to write piece-wise functions
. . with a "brace" at the left end only.

f(x) = \begin{Bmatrix} x+3 & x < 2 \\ 6-x & x \ge 2 \end{array}

$f(x) = \begin{Bmatrix} x+3 & x < 2 \\ 6-x & x \ge 2 \end{array}$

4. ## Re: testing

Wow so many different ways. I have to throw in my two cents

$f(x) = \begin{cases} x+3, \quad x < 2 \\ 6-x. \quad x \ge 2 \end{cases}$

f(x) = \begin{cases} x+3, \quad x < 2 \\ 6-x. \quad x \ge 2 \end{cases}